The Critical Role of Leadership in Patient Safety Culture: A Mediation Analysis of Management Influence on Safety Factors [Corrigendum] - Huang CH; Wu HH; Lee YC; Li X (Dove Medical Press, 2024)
Huang CH, Wu HH, Lee YC, Li X. Risk Manag Healthc Policy. 2024;17:513–523. The authors have advised that the affiliation list on page 513 is incorrect. Affiliation list number 6, the text “Hung Kuang University” should read “Hungkuang University”. The authors have also advised that the correspondence address on page 513 is incorrect. The text “Hung Kuang University, No. 34 Zhongqi Road, Shalu District, Taichung City, Taiwan” should read “Hungkuang University, No. 1018, Sec. 6, Taiwan Boulevard, Shalu District, Taichung City 433304, Taiwan”. The authors apologise for this error.